Time intensive cognitive behavioural therapy for a specific phobia of vomiting: A single case experimental design. (March 2020) - Keyes, Alexandra; Deale, Alicia; Foster, Chloe; Veale, David
Abstract: Background and Objectives: Specific Phobia of Vomiting (SPOV) may be difficult to treat, and to date only one RCT has been published. Specific Phobias can be successfully treated using time intensive treatment formats. Imagery rescripting (ImRs) has also been shown to be a successful component for treating various anxiety disorders. The present study aims to evaluate the effectiveness of time intensive CBT and ImRs at reducing symptoms in SPOV. Methods: A multiple baseline ABCADE single case experimental design (SCED) was used to monitor symptoms across time in eight participants. The Specific Phobia of Vomiting Inventory (SPOVI) was administered to measure SPOV symptoms at each clinical session. Visual analysis of graphed data was used to compare data across treatment phases. Reliable and clinically significant change was also calculated on the SPOVI at 6-month follow up. Results: Findings suggest that time intensive CBT is associated with improvements across symptoms of SPOV. There was limited support for ImRs in the current study; however, informal discussion of aversive memories of vomiting, and formulation of the problem may be helpful in its own right in treatment of SPOV. Seven out of eight participants (87.5%) achieved reliable improvement and five (62.5%) achieved clinically significant change on the SPOVI at 6-month follow up. Time intensive treatment was associated with high client satisfaction ratings. Limitations: Limitations include lack of measurement of therapist adherence to protocol, and a short period of daily symptom monitoring in between ImRs and intensive treatment phases. Conclusions: Time intensive CBT including an ImRs component may be an effective and acceptable treatment in reducing SPOV symptomatology. Further research using larger sample sizes in a RCT is needed. Highlights: Research into effective treatments for specific phobia of vomiting is limited to date. Time intensive treatments has been shown to be effective in other specific phobias. Time intensive cognitive behavioural therapy associated with improvement in 8 cases. Further study by randomised control trial is needed.